2016
DOI: 10.1038/ncomms13683
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid metabolic reprogramming via mTOR-mediated inductions of PPARγ directs early activation of T cells

Abstract: To fulfil the bioenergetic requirements for increased cell size and clonal expansion, activated T cells reprogramme their metabolic signatures from energetically quiescent to activated. However, the molecular mechanisms and essential components controlling metabolic reprogramming in T cells are not well understood. Here, we show that the mTORC1–PPARγ pathway is crucial for the fatty acid uptake programme in activated CD4+ T cells. This pathway is required for full activation and rapid proliferation of naive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
163
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(184 citation statements)
references
References 48 publications
10
163
2
Order By: Relevance
“…Activation of mTOR, a major regulator of metabolic pathway utilization and T cell activation, was recently demonstrated by Besnard et al to be essential for induction of latent HIV in human CD4 T cells [120]. Rasheed et al showed that HIV replication upregulates lipid metabolism pathways and production of free fatty acids in infected human CD4 T cells, and consistent with this study, Angela et al showed that fatty acid metabolism through mTOR and PPARγ activation is critical for maximal activation of human CD4 T cells [121, 122]. CD4 T regulatory cells, important regulators of adipose tissue homeostasis as well representing a cellular reservoir for latent HIV, preferentially utilize oxphos and recent studies have demonstrated that Foxp3 promotes activation of oxphos and fatty acid oxidation pathways [123126].…”
Section: Immunometabolism Metabolic Reprogramming and Relevance For supporting
confidence: 73%
“…Activation of mTOR, a major regulator of metabolic pathway utilization and T cell activation, was recently demonstrated by Besnard et al to be essential for induction of latent HIV in human CD4 T cells [120]. Rasheed et al showed that HIV replication upregulates lipid metabolism pathways and production of free fatty acids in infected human CD4 T cells, and consistent with this study, Angela et al showed that fatty acid metabolism through mTOR and PPARγ activation is critical for maximal activation of human CD4 T cells [121, 122]. CD4 T regulatory cells, important regulators of adipose tissue homeostasis as well representing a cellular reservoir for latent HIV, preferentially utilize oxphos and recent studies have demonstrated that Foxp3 promotes activation of oxphos and fatty acid oxidation pathways [123126].…”
Section: Immunometabolism Metabolic Reprogramming and Relevance For supporting
confidence: 73%
“…Glucose is not the only nutrient used by T n cells, which can also oxidize external lipids like oleate and palmitate in their mitochondria (23, 24). To this end, T n cells express enzymes that support the oxidation of long-chain fatty acids (LCFAs) (25), and metabolomic analysis of these cells found abundant acylcarnitine molecules, which correlate with this process (24, 26). …”
Section: Metabolic Changes Defining Cd8+ T Cell Immunitymentioning
confidence: 99%
“…Lipids and fatty acids are also critical nutrients for lymphocytes; not only are they integral components of cell membranes, but they are also a high energy source [21,22]. To date, the overarching theme in lymphocyte metabolism is that, as opposed to the glycolytic phenotype of activated effector T cells, memory and regulatory T cells can also metabolize amino acids and fatty acids, and generate ATP through OXPHOS.…”
Section: Metabolism and Its Regulation In Lymphocytesmentioning
confidence: 99%